Explorer la sobriété : Enquête participative en contexte de crise énergétique - Maxime Cordellier; Michelle Dobré (VertigO)
The involuntary “collective sobriety” announced in France for the winter of 2022-2023 provided an opportunity to discuss various energy transition scenarios in the public arena, and to review the notion of sobriety. Following a methodology specific to participatory science (living lab), we questioned lay representations of the current challenges of the energy crisis. Four participatory workshops held in the city of Caen enabled us to explore the world of solutions envisaged by contributors. We identified four themes that raised questions for the audiences taking part in the workshops: over-consumption; lifestyles understood as materializations of the dominant social organization; the regulatory framework for energy-guzzling practices; and the question of democratic decision-making levels. Confronted with the challenges of energy sobriety, the imaginations of change are divided between individual and collective solutions, between institutional regulation and voluntary or involuntary restrictions. Four types of response have been proposed: increased regulations on use; a call for political voluntarism and exemplarity from elites; education in sobriety; and the transformation of uses and lifestyles. This article examines the social motivations behind the representations of problems and solutions that have emerged in participatory workshops organized using the living lab method. It will also discuss the interests and limits of the living lab methodology for accessing the driving forces behind social innovations.